Quantification of anandamide, oleoylethanolamide and palmitoylethanolamide in rodent brain tissue using high performance liquid chromatographyâelectrospray mass spectroscopy - Daniel J. Liput; Eleftheria Tsakalozou; Dana C. Hammell; Kalpana S. Paudel; Kimberly Nixon; Audra L. Stinchcomb (Elsevier, 2014)
Reported concentrations for endocannabinoids and related lipids in biological tissues can vary greatly; therefore, methods used to quantify these compounds need to be validated. This report describes a method to quantify anandamide (AEA), oleoylethanolamide (OEA) and palmitoylethanolamide (PEA) from rodent brain tissue. Analytes were extracted using acetonitrile without further sample clean up, resolved on a C18 reverse-phase column using a gradient mobile phase and detected using electrospray ionization in positive selected ion monitoring mode on a single quadrupole mass spectrometer. The method produced high recovery rates for AEA, OEA and PEA, ranging from 98.1% to 106.2%, 98.5% to 102.2% and 85.4% to 89.5%, respectively. The method resulted in adequate sensitivity with a lower limit of quantification for AEA, OEA and PEA of 1.4Â ng/mL, 0.6Â ng/mL and 0.5Â ng/mL, respectively. The method was reproducible as intraday and interday accuracies and precisions were under 15%. This method was suitable for quantifying AEA, OEA and PEA from rat brain following pharmacological inhibition of fatty acid amide hydrolase. Keywords: Endocannabinoids, Acylethanolamides, Anandamide, OEA, PEA, LCâMS